Building Dynamics CRM 2015 dashboards with Power BI : build interactive and analytical sales productivity dashboards for Dynamics CRM 2015 with Power BI /: build interactive and analytical sales productivity dashboards for Dynamics CRM 2015 with Power BI. (2015) - Ivie, Steve
No abstract available